MEANINGS OF PREPOSITIONS OVER, ABOVE, UNDER, BELOW IN ENGLISH AND THE VIETNAMESE EQUIVALENTS FROM A COGNITIVE SEMANTICS PERSPECTIVE / Đào Thị Hương; GVHD: Hoang Tuyet Minh - Đào, Thị Hương
The thesis studies the meanings of four vertical prepositions above, over, below, and under to find out their similarities and differences. The theory of cognitive linguistics and cognitive semantics are used as fundamental framework background for the research. The data are collected and analyzed in three famous literary works that are represented by the tables and figures. They were grouped and analyzed through using image schemas (analyzing spatial senses) and metaphorical structures (analyzing metaphorical expressions or non-spatial senses). Investigating of four described prepositions through the up-down schema gave the results but there are still some differences in characteristics of the trajector and the landmark and the Vietnamese equivalents of these prepositions. These differences cause different spatial senses and metaphorical uses of the prepositions and synonyms that made some common errors by the first year non-major students at The Police People University of Technology and Logistics. Because we also have limited in time and referential documents, especially in literary works, which considered as only the results of prepositional analysis in form of (NP) + in + NP and NP + V + in + NP in the thesis. Therefore, it is necessary to have better further research to: (i) study some issues of prepositions based on the cognitive theory of previous studies in this thesis. (ii) investigate the meanings of the whole lexical units of above, over, below, and under where they function as a preposition, an adverb and prefix to propose a clearer and more profound radial network of the prepositions